Serial ASPECTS in the DAWN Trial: Infarct Evolution and Clinical Impact. Issue 10 (October 2021) - Liebeskind, David S.; Saber, Hamidreza; Bhuva, Parita; Xiang, Bin; Yoo, Albert J.; Jadhav, Ashutosh P.; Haussen, Diogo C.; Budzik, Ronald F.; Bonafe, Alain; Yavagal, Dileep R.; Hanel, Ricardo A.; Ribo, Marc; et al.
Abstract : Background and Purpose: The impact of baseline ischemia on Alberta Stroke Program Early CT Score (ASPECTS) and evolution over 24 hours may be distinct in late thrombectomy. We analyzed predictors of serial ASPECTS and clinical outcomes in the DAWN trial (Diffusion-Weighted Imaging or CTP Assessment With Clinical Mismatch in the Triage of Wake-Up and Late Presenting Strokes Undergoing Neurointervention With Trevo). Methods: The DAWN Imaging Core Laboratory independently scored ASPECTS at baseline and 24 hours. Descriptive statistics characterized ASPECTS on computed tomography/magnetic resonance imaging at baseline and 24 hours, delineating ASPECTS change over 24 hours. Results: 206 subjects (mean age 70.0±13.7 years; 54.9% (n=113) female; baseline National Institutes of Health Stroke Scale median (interquartile range) 17 (13, 21) were included. Baseline ASPECTS was median (interquartile range) 8.0 (7–8), with 92/205 (44.9%) between 0 and 7 and 113/205 (55.1%) 8 and 10. 24-hour ASPECTS was median 6.0 (4–8), with ASPECTS change or infarct evolution having median −1, ranging from −8 to +2. Multivariable logistic regression showed older age (odds ratio [OR] for 10-year interval, 1.26 [95% CI, 1.02–1.55], P =0.030) and dyslipidemia (OR, 1.84 [95% CI, 1.06–3.19], P =0.031) were independently associated with higher baseline ASPECTS. Higher 24-hour ASPECTS was predicted by endovascular treatment (OR, 2.76 [95% CI, 1.58–4.81], P =0.0004), baseline glucose <150 mg/dL (OR, 2.86 [95% CI, 1.50–5.46], P =0.001), lower baseline National Institutes of Health Stroke Scale (OR, 0.93 [95% CI, 0.89–0.98], P =0.010), and older age (OR for 10-year interval, 1.25 [95% CI, 1.01–1.55], P =0.041). Internal carotid artery lesion location (OR, 0.47 [95% CI, 0.24–0.89], P =0.021) was inversely related to 24-hour ASPECTS. Good clinical outcome (day 90 modified Rankin Scale score 0–2) was predicted by 24-hour ASPECTS (OR, 1.46 [95% CI, 1.08–1.96], P =0.014). Extensive infarct evolution (ASPECTS decrease ≥6) occurred in 14/201 (7.0%). Elevated baseline serum glucose ≥150 mg/dL was a predictor of ASPECTS decrease of ≥4 points (OR, 2.78 [95% CI, 1.21–6.35] P =0.016) as was internal carotid artery occlusion (OR, 2.49 [95% CI, 1.05–5.88]; P =0.038). ASPECTS change was influenced by treatment arm ( P =0.001 by Wilcoxon), including 0 ASPECTS change in 42/105 (40.0%) of the endovascular arm and only 20/96 (20.8%) of the medical arm. Conclusions: DAWN subjects enrolled with small infarct cores had a broad range of baseline ASPECTS. Twenty-four-hour ASPECTS, strikingly influenced by endovascular therapy, predicted good clinical outcomes. Registration: https://www.clinicaltrials.gov ; Unique identifier: NCT02142283.